Biotechnological Approaches on Engineering Medicinal Tropane Alkaloid Production in Plants - Gong, Haiyue; He, Ping; Lan, Xiaozhong; Zeng, Lingjiang; Liao, Zhihua (Frontiers in Plant Science, 2022)
Hyoscyamine and scopolamine, belonging to medicinal tropane alkaloids (MTAs), are potent anticholinergic drugs. Their industrial production relies on medicinal plants, but the levels of the two alkaloids are very low in planta. Engineering the MTA’s production is an everlasting hot topic for pharmaceutical industry. With understanding the MTA’s biosynthesis, biotechnological approaches are established to produce hyoscyamine and scopolamine in an efficient manner. Great advances have been obtained in engineering MTA’s production in planta. In this review, we summarize the advances on the biosynthesis of MTAs and engineering the MTA’s production in hairy root cultures, as well in plants. The problems and perspectives on engineering the MTA’s production are also discussed.